The nutritional impact of a feeding protocol for infants on high flow nasal cannula therapy. (24th January 2022) - Walter, Sarah; DeLeon, Stephanie; Walther, Jonathan P.; Sifers, Felicia; Garbe, Michael Connor; Allen, Christine
Abstract: Background: Clinicians may be reluctant to feed patients on high‐flow nasal cannula (HFNC) therapy, despite studies suggesting it is beneficial and safe. We describe the implementation of a feeding protocol for patients with bronchiolitis on HFNC and determine its effect on nutrition goals. Methods: Prospective bedside data on enteral volume, feed interruptions, and aspiration events were collected on patients with bronchiolitis who were <24 months of age, treated with HFNC, and fed per a developed protocol. Exclusion criteria included history of prematurity <32 weeks, congenital heart disease, or positive‐pressure ventilation before feeding. Length of intensive care unit and hospital stay was compared with both a concurrent cohort (CC) of patients not fed per the protocol and a retrospective cohort (RC) admitted prior to protocol creation. Results: Seventy‐eight patients met the criteria for the prospective study arm: 24 patients were included in the CC, and 74 were included in the RC. Seventy‐one percent of prospective patients received enteral nutrition (EN) on HFNC day 1 vs 42% of the CC. In the prospective cohort, feed interruption occurred in 23% of patients and was associated with higher flow rates; however, no aspiration events occurred. Patients fed per protocol were fed 8–10 h sooner and discharged 1 day earlier than those in the RC. Conclusion: The use of a feeding protocol for patients with bronchiolitis on HFNC was safe and associated with shorter time to initiate EN and shorter length of hospital stay.